Procurement and supply chain management - Lysons, Kenneth; Farrington, Brian (Pearson, 2020)
"Dr Brian Farrington is the author of the tenth edition of this acclaimed book. The output of any book is influenced by many sources, including: - professional feedback from lecturers at Universities and Colleges; their views are invaluable - the Chartered Institute of Procurement and Supply's education syllabus and the Institute's continual quest to enhance standards - legal challenges to procurement decisions - emphasis on environmental and socially responsible procurement - feedback from learners and practitioners - the author's international consultancy experience - the recognition that a procurement specialist has to exercise the highest moral and ethical standards and that some fall short - the challenge presented by cyber security. There are two new chapters, thanks to the foresight of Pearson. Public Sector Procurement is a new chapter, recognising the public sector's impact on the global economy. Public accountability means that scrutiny of decisions is far more open than the private sector. Sustainability & Socially Responsible Procurement is a new chapter, recognising that this is a highly challenging global issue wherein procurement has great influence. More initiatives are necessary. There has been a serious recasting of much of the content. There is an unrivalled opportunity for procurement specialists to manage risk, finance and corporate performance. The author seeks to instil in all procurement specialists the fact that effective and innovative procurement pays a significant part in the management of economies and corporate performance. A01"--